A new furostanol saponin from Dendrobium chrysanthum Lindl. with cytotoxic activity. Issue 17 (2nd September 2019) - Yang, Chao; Lin, Weilong; Zhao, Lin; Cai, Jinyan
Abstract: A new furostanol saponin, (25 R )-26- O -( α -d- glucopyranosyl)-(1→2)- α -l -rhamnopyranosyl-furost-5-ene-3 β, 22 α, 26-triol-3- O - α -d- glucopyranoside (1 ), together with four known compounds2–5 were isolated from the ethanolic extract of the stems of Dendrobium chrysanthum Lindl . The structures of these new compounds were identified by extensive spectroscopic analysis including 1D and 2D NMR and HR-ESI-MS, as well as chemical methods. Compounds1–3 were isolated from D. chrysanthum for the first time. Furthermore, the inhibitory effects of the compounds on tumor cells were evaluated, and compounds1–2 exhibited significant cytotoxic activities potentially against SPC-A1, MCF-7 and HeLa human cancer cell lines. Compounds3–5 showed inhibitory activity against the SPC-A1 and MCF-7. Abstract :